2017
DOI: 10.1111/grs.12161
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the distribution of lactic acid bacteria on Pennisetum grasses

Abstract: Successful silage production depends on the promotion of lactic acid fermentation and one of the key factors influencing the fermentation quality of silage is lactic acid bacteria (LAB). Therefore, epiphytic LAB on grasses play an important role in silage production. The present research investigated the distribution of LAB on Pennisetum spp. and factors influencing its presence. Lactic acid bacteria on four grass cultivars, cv. MT‐1, cv. Mott, cv. Reyan No. 4 (Reyan) and cv. Guimu No. 1 (Guimu), were investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 25 publications
4
9
0
Order By: Relevance
“…Generally, lactic acid bacterial strains produce higher amount of lactic acid than acetic acid. The amount of organic acid produced by LAB strain directly decides its fermentation quality (Chen et al 2017). Similarly, in this study, KCC-30 fermented L. multiflorum forage soup under anaerobic condition better than that under aerobic conditions.…”
Section: Discussionsupporting
confidence: 54%
“…Generally, lactic acid bacterial strains produce higher amount of lactic acid than acetic acid. The amount of organic acid produced by LAB strain directly decides its fermentation quality (Chen et al 2017). Similarly, in this study, KCC-30 fermented L. multiflorum forage soup under anaerobic condition better than that under aerobic conditions.…”
Section: Discussionsupporting
confidence: 54%
“…In previous studies, regardless of enriching lactic acid bacteria in fresh raw materials (Chen et al, 2017) or adding external lactic acid bacteria artificially during ensiling (Zhang et al, 2020), relative abundance or cultivable quantity of various species of microorganisms have been the principal consideration rather than metabolic functions. Thus, there might be some neglected effects from additives or environmental factors in the silage fermentation process.…”
Section: Discussionmentioning
confidence: 99%
“…Growth of LAB isolate at different pH values, salts concentrations and temperatures were observed by using MRS broth. Carbohydrate fermentation profile was determined by using API 50 CHL ® (bioMérieux, L' Etoile, France) kit, whereas 16S rRNA gene sequences were determined as described previously by Chen et al (2017). The nucleotide sequences for the 16S rRNA genes described in this report were deposited in GenBank under accession numbers as follows: KC845196, KC845200, MT894302, MT894301, KC845202, MT894299, MT894300 and KC845204 for the representative isolates of 20.1, Ban4, Guo1, CK5, CK2, N2, CK3 and 10.1, respectively.…”
Section: Isolation and Identification Of Lab Strainsmentioning
confidence: 99%
“…There are a few reports on LAB communities that present on different forage crops (Khota et al, 2016; Pang et al, 2012). Our previous study showed that the species composition and abundance of LAB differed among four Pennisetum grasses, and the number of LAB was positively correlated with the WSC content of grass (Chen et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation